Citizen Traceability: Surveillance à la Argentina - Avaro, Dante Adalberto (2014)
The Argentine Republic have since the year 2011 a Federal System of BiometricIdentification for Security (SIBIOS). From this fact the Mr. Julian Assange said that Argentina has an aggressive surveillance system. In this article we will show you what in reality Argentina has arrange as policy of identification that allows the State to track the behavior of its citizens from varied and multiple windows than governmental and private. We call this policy of citizen identification as traceability. Therefore SIBIOS appears as a new and complementary device that is constantly evolving and we have to wait until it evolves.